Stability of Commercially Available Macular Carotenoid Supplements in Oil and Powder Formulations - Phelan, David (Nutrients, 2017)
We previously identified that the concentration of zeaxanthin in some commercially available carotenoid supplements did not agree with the product’s label claim. The conclusion of this previous work was that more quality assurance was needed to guarantee concordance between actual and declared concentrations of these nutrients i.e., lutein (L) zeaxanthin (Z) and meso-zeaxanthin (MZ) in commercially available supplements. Since this publication, we performed further analyses using different commercially available macular carotenoid supplements. Three capsules from one batch of eight products were analysed at two different time points. The results have been alarming. All of the powder filled products (n = 3) analysed failed to comply with their label claim (L: 19–74%; Z: 57–73%; MZ: 83–97%); however, the oil filled soft gel products (n = 5) met or were above their label claim (L: 98–122%; Z: 117–162%; MZ: 97–319%). We also identified that the carotenoid content of the oil filled capsules were stable over time (e.g., L average percentage change: −1.7%), but the powder filled supplements degraded over time (e.g., L average percentage change: −17.2%). These data are consistent with our previous work, and emphasize the importance of using carotenoid interventions in oil based formulas rather than powder filled formulas.